National Insights and Youth Political Attitudes in Rural Lampung Against Negative Campaigns - Hertanto Hertanto; Handi Mulyaningsih; Asep Nurjaman (Universitas Muhammadiyah Tangerang, 2021)
Indonesia is a heterogeneous country that requires an inclusive and tolerant attitude to live in harmony. However, with the implementation of direct elections in Indonesia, there are many hoaxes and black campaigns through the mass media. The purpose of this study is to examine the national insight and political attitudes of rural youth in social media-based election campaigns. The method used is in-depth interviews through structured focus group discussions (FGD) with young students in rural South Lampung. The results showed that Lampung rural youth realized the importance of Pancasila as a unifying tool for the nation. Furthermore, the youth of Lampung strongly disapprove of hoaxes and black campaigns in the general election. This finding is very important to maintain harmony in Indonesia and can serve as a model Indonesia merupakan negara heterogen yang membutuhkan sikap inklusif dan toleran agar dapat hidup rukun. Namun, dengan diterapkannya pemilihan langsung di Indonesia, banyak bermunculan hoax dan kampanye hitam melalui media massa. Tujuan penelitian ini adalah untuk mengkaji wawasan kebangsaan dan sikap politik pemuda pedesaan dalam kampanye pemilu berbasis media sosial. Metode yang digunakan adalah wawancara mendalam melalui diskusi kelompok terfokus (FGD) terstruktur dengan mahasiswa generasi muda di pedesaan Lampung Selatan. Hasil penelitian menunjukkan bahwa pemuda pedesaan Lampung menyadari pentingnya Pancasila sebagai alat pemersatu Bangsa. Lebih lanjut, pemuda Lampung sangat tidak setuju dengan hoaks dan kampanye hitam dalam pemilihan umum. Temuan ini sangat penting untuk menjaga kerukunan di Indonesia dan dapat menjadi model bagi daerah lain di Indonesia.